Costunolide Reduces DN Inflammatory Response and Renal Thrombosis by Inhibiting NET Formation - Xiangjing Wang; Lina Zhang; Ke Huang; Chengli Lou; Yuanying Xia; Yijing Zhou (Journal of Diabetes Research)
Conclusion: COS alleviates inflammation and platelet activation–mediated thrombosis in DN mice, potentially by inhibiting excessive NET formation. These findings highlight the therapeutic potential of COS in managing DN.